Circadian Rhythm of VIP in Chicken Intrinsic Choroidal Neurons - Hohberger, Bettina; Lessberger, Carmen; Hermann, Franz; Zenkel, Matthias; Bergua, Antonio; Neuhuber, Winfried (2016)
EVALuna2:184249

VIP changes during daytime in chicken intrinsic choroidal neurons - Hohberger, Bettina; Jeßberger, Carmen; Hermann, Franz; Zenkel, Matthias; Kaser-Eichberger, Alexandra; Bergua, Antonio; Juenemann, Anselm G.; Schrödl, Falk; Neuhuber, Winfried (Experimental Eye Research, 2018)
PURPOSE: Ocular autonomic control is mediated by sympathetic and parasympathetic nerve fibres. Their interactions are complemented by primary afferent nerve fibers of and intrinsic choroidal neurons (ICN). As the vasodilatative neuropeptide, vasoactive intestinal peptide (VIP), is expressed in extrinsic and intrinsic ocular neurons, it is of special interest in ophthalmic research. Since circadian changes of ocular blood flow are known in humans and birds, this study aimed at investigating VIP expression at different daytimes in chicken choroid, the preferred model species in ICN research. METHODS: 12 eyes of 12 chickens were retrieved, slaughtered at 8.00-9.30 a.m. (n = 6) and 8.00 p.m. (n = 6), respectively, and choroidal wholemounts were prepared for immunofluorescence of VIP. VIP-positive ICN of both groups were quantified and density of VIP-positive axons assessed semi-quantitatively. In 28 additional eyes retrieved in the morning (n = 14) and evening (n = 14), choroidal VIP content was determined by ELISA. Morning and evening data were analyzed statistically. NADPH-diaphorase (NADPH-d, ICN cell marker) was done at additional 12 whole mount choroids of 12 chicken, retrieved in the morning (n = 6) and evening (n = 6). RESULTS: (1) Numbers of VIP positive neurons differed significantly between morning: (239.17 ± 113.9) and evening: (550.83 ± 245.7; p = 0.018). (2) Numbers of VIP-positive perikarya were significantly more accumulated in the temporal part of the choroid in the evening than in the morning (p = 0.026). (3) VIP positive axon density was found to be similar throughout the choroid in the morning and evening. (4) Number of NADPH-d positive neurons was not significantly different between morning (848.8 ± 399.5) and evening (945.8 ± 622.1, p > 0.05). (5) ELISA demonstrated a significant difference of VIP content (p = 0.012) in tissues harvested in the morning (145.41 ± 43.3 pg/ml) compared to evening (221.44 ± 106.3 pg/ml). CONCLUSIONS: As VIP positive axon density was similar in the morning and the evening throughout the choroid, PPG and ICN seemed to contribute equally to the axon network. Yet, changes in the total choroidal VIP content, the numbers of VIP positive perikarya, reflecting the intracellular VIP content, and their topographical distribution at two different days-times argue for a different status of activation of both neuronal sources in contrast to the equal amount of NADPHD-d positive neurons. The higher VIP content in the evening, compared to the morning, correlates with a known circadian rhythm of a lower IOP and a higher choroidal thickness at night. Thus, these changes may argue for a potential role of ICN in the regulation of ocular homeostasis and integrity.
EVALuna2:34748